2014
DOI: 10.1002/adfm.201401478
|View full text |Cite
|
Sign up to set email alerts
|

An Easily Sintered, Chemically Stable, Barium Zirconate‐Based Proton Conductor for High‐Performance Proton‐Conducting Solid Oxide Fuel Cells

Abstract: Yttrium and indium co‐doped barium zirconate is investigated to develop a chemically stable and sintering active proton conductor for solid oxide fuel cells (SOFCs). BaZr0.8Y0.2‐xInxO3‐ δ possesses a pure cubic perovskite structure. The sintering activity of BaZr0.8Y0.2‐xInxO3‐ δ increases significantly with In concentration. BaZr0.8Y0.15In0.05O3‐ δ (BZYI5) exhibits the highest total electrical conductivity among the sintered oxides. BZYI5 also retains high chemical stability against CO2, vapor, and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 78 publications
2
38
0
Order By: Relevance
“…Various authors have shown that ZnO, CuO, and In 2 O 3 are the promising sintering aid for these oxides [6][7][8][9][10][11][12]. S. Tao and J.T.S.…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have shown that ZnO, CuO, and In 2 O 3 are the promising sintering aid for these oxides [6][7][8][9][10][11][12]. S. Tao and J.T.S.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 The high OCV values indicate the dense nature of the BZYNi04 electrolyte membrane (12 μm in thickness) allowing for no gas leakage. Applying humidified hydrogen (≈ 3% H 2 O) as the fuel and static air as the oxidant, a maximum power density of 428, 340, 240, 160 and 94 mW cm −2 was obtained at 700, 650, 600, 550 and 500 37 electrolyte, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 The high OCV values indicate the dense nature of the BZYNi04 electrolyte membrane (12 μm in thickness) allowing for no gas leakage. Applying humidified hydrogen (≈ 3% H 2 O) as the fuel and static air as the oxidant, a maximum power density of 428, 340, 240, 160 and 94 mW cm −2 was obtained at 700, 650, 600, 550 and 500 37 electrolyte, respectively. It should be emphasized that, to the best of our knowledge, the power performance obtained in this study is one of the best reported thus far for thermodynamically stable BaZrO 3 -based proton conducting SOFCs, and is compared with the recent literature reports as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, doped BaCeO 3 oxides in general show poor chemical stability under CO 2 or steam containing atmospheres, and therefore the trade-offs are proposed with a goal to adjust chemical stability of the BaCeO 3 -based oxides at the expense of the proton conductivity [9,10]. In contrast, acceptor-doped BaZrO 3 oxides owning acceptable conductivity have been already proven to be excellent chemical stability under SOFCs working condition, which might be more suitable for practical applications [11][12][13][14]. However, the serious sintering activity of BaZrO 3 oxides usually generates a large volume of highly resistive grain boundaries.…”
Section: Introductionmentioning
confidence: 99%